2020
DOI: 10.3390/nu12092822
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal, Gastric, and Duodenal Histologic Findings in Patients with Feeding Difficulties

Abstract: Currently, there are inconsistencies in the recommendations of when to obtain an esophagogastroduodenoscopy (EGD) in children with feeding difficulties. The aim of our study was to identify EGD findings in patients presenting to a large, outpatient feeding program. Additionally, we investigated the presence of any relationship between abnormal pathology seen on biopsies (inflammation) and symptoms of feeding intolerance such as vomiting, gagging, retching, or abdominal pain. Retrospective analysis of electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A recent study in pediatric patients with rumination syndrome demonstrated increased eosinophil and mast cell densities in the gastric antrum [12]. Reports indicate a high proportion of patients with feeding difficulties who have undergone esophagogastroduodenoscopy (EGD), demonstrate some degree of inflammation on biopsies [4,13], with a subset including those with eosinophilia [14]. It is unknown whether mast cell density and eosinophilia contribute to symptoms of decreased volume or variety of foods ingested in these children.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in pediatric patients with rumination syndrome demonstrated increased eosinophil and mast cell densities in the gastric antrum [12]. Reports indicate a high proportion of patients with feeding difficulties who have undergone esophagogastroduodenoscopy (EGD), demonstrate some degree of inflammation on biopsies [4,13], with a subset including those with eosinophilia [14]. It is unknown whether mast cell density and eosinophilia contribute to symptoms of decreased volume or variety of foods ingested in these children.…”
Section: Introductionmentioning
confidence: 99%